Limited energy supply, sunspots, and monetary policy - Nils Gornemann; Sebastian Hildebrand; Keith Küster (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
A common assumption in macroeconomics is that energy prices are determined in a world-wide, rather frictionless market. This no longer seems an adequate description for the situation that much of Europe currently faces. Rather, one reading is that shortages exist in the quantity of energy available. Such limits to the supply of energy mean that the local price of energy is affected by domestic economic activity. In a simple open-economy New Keynesian setting, the paper shows conditions under which energy shortages can raise the risk of self-fulfilling fluctuations. A firmer focus of the central bank on input prices (or on headline consumer prices) removes such risks.
Keywords: E31; E32; E52; F41; Q43; 330; Energy crisis; macroeconomic instability; sunspots; monetary policy; heterogeneous households